1984
DOI: 10.1159/000249708
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia areata: A Clinical Study

Abstract: 100 cases of alopecia areata are examined and the possible relationship with the presumed etiological factors (atopy, autoimmunity and psychosomatics) are looked for. When atopy or autoantibodies are present alopecia areata always runs a severe course. It is, however, impossible to establish a definite etiological relation between atopy or autoimmunity and alopecia areata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 8 publications
2
21
1
2
Order By: Relevance
“…This frequency was significantly higher than that found in the normal population in our area (11.9%; p =0.0212). These patients had a significantly higher incidence of vitiligo in their families (76.9 vs. 29.7% of the nonatopic; p<0.025), an earlier onset (14.1 vs. 24 years of the nonatopic) and a rapid worsening of the disease.Vitiligo is frequently associated with alopecia areata 11, 2]; this in turn is frequently associated with atopy [3][4][5][6][7]; moreover, the atopic type of alopecia areata of Ikeda's classification |4| is characterized by an earlier onset [4,8], a worse prognosis and response to topical immunomodulators [8], Association between vitiligo and atopic manifestations has only indirectly been reported in a study of alopecia areata [3], and more recent studies of atopic dermatitis do not report a significantly increased frequency of the asso ciation of vitiligo and atopic dermatitis [9J.We searched for atopy in patients suffering from vit iligo and correlated its presence with some clinical param eters of the latter. …”
mentioning
confidence: 99%
“…This frequency was significantly higher than that found in the normal population in our area (11.9%; p =0.0212). These patients had a significantly higher incidence of vitiligo in their families (76.9 vs. 29.7% of the nonatopic; p<0.025), an earlier onset (14.1 vs. 24 years of the nonatopic) and a rapid worsening of the disease.Vitiligo is frequently associated with alopecia areata 11, 2]; this in turn is frequently associated with atopy [3][4][5][6][7]; moreover, the atopic type of alopecia areata of Ikeda's classification |4| is characterized by an earlier onset [4,8], a worse prognosis and response to topical immunomodulators [8], Association between vitiligo and atopic manifestations has only indirectly been reported in a study of alopecia areata [3], and more recent studies of atopic dermatitis do not report a significantly increased frequency of the asso ciation of vitiligo and atopic dermatitis [9J.We searched for atopy in patients suffering from vit iligo and correlated its presence with some clinical param eters of the latter. …”
mentioning
confidence: 99%
“…Pozitif aile öyküsü yapılan yayınlarda %4.6 ile %42 arasında değişmektedir (5,16,17). Küçük yayınlarda aile öyküsü görülme sıklığı daha fazla bulunmuştur (18)(19)(20). Bizim çalışmamızda 54 AA'lı hastanın 16'sında (%29.6) aile öyküsü mevcuttu.…”
Section: Discussionunclassified
“…24,32 Juvenile onset AA, also characterized by a bad natural history and poor response to treatment (41.5%), confirms earlier studies. [23][24][25]27,28,[42][43][44] Atopy in AA has been reported to be one of the bad prognostic factors. 24,33,34 In contrast, this study showed no statistically significant differences between the atopic and nonatopic groups according to response rate and severity (Tables 1 and 3).…”
Section: Discussionmentioning
confidence: 99%